Characterization of N2O emissions and associated microbial communities from the ant mounds in soils of a humid tropical rainforest - Majeed, M Z; Miambi, E; Barois, I; Bernoux, M; Brauman, A (Folia microbiologica, 2018)
Tropical rainforest soils harbor a considerable diversity of soil fauna that contributes to emissions of N2O. Despite their ecological dominance, there is limited information available about the contribution of epigeal ant mounds to N2O emissions in these tropical soils. This study aimed to determine whether ant mounds contribute to local soil N emissions in the tropical humid rainforest. N2O emission was determined in vitro from individual live ants, ant-processed mound soils, and surrounding reference soils for two trophically distinct and abundant ant species: the leaf-cutting Atta mexicana and omnivorous Solenopsis geminata. The abundance of total bacteria, nitrifiers (AOA and AOB), and denitrifiers (nirK, nirS, and nosZ) was estimated in these soils using quantitative PCR, and their respective mineral N contents determined. There was negligible N2O emission detected from live ant individuals. However, the mound soils of both species emitted significantly greater (3-fold) amount of N2O than their respective surrounding reference soils. This emission increased significantly up to 6-fold in the presence of acetylene, indicating that, in addition to N2O, dinitrogen (N2) is also produced from these mound soils at an equivalent rate (N2O/N2 = 0.57). Functional gene abundance (nitrifiers and denitrifiers) and mineral N pools (ammonium and nitrate) were significantly greater in mound soils than in their respective reference soils. Furthermore, in the light of the measured parameters and their correlation trends, nitrification and denitrification appeared to represent the major N2O-producing microbial processes in ant mound soils. The ant mounds were estimated to contribute from 0.1 to 3.7% of the total N2O emissions of tropical rainforest soils.
Keywords: Animals; N-cycle genes; Microbial denitrification; Nitrification; Ants; Tropical forest soil; bakteriální geny; nitrifikace; Formicidae; půdní mikrobiologie; deštný prales; Nitrous Oxide; Bacteria; Nitrous oxide emission; Soil Microbiology; Genes, Bacterial; Atta mexicana; Soil; zvířata; půda; Denitrification; oxid dusný; Rainforest; Solenopsis geminata; Ant mounds; denitrifikace